Hunting Charles Manson : the quest for justice in the days of helter skelter - Wiehl, Lis W (Nelson Books, an imprint of Thomas Nelson, 2018)
New York Times bestselling author and former federal prosecutor Lis Wiehl uses new research and first-hand interviews to tell the heart-pounding story of Charles Manson's horrific crimes, the painstaking investigation that followed, and the inspired prosecution that put him away.--